Local special findings in domestic contexts of a frontier post in the Egyptian delta. The small finds of Tell El-Ghaba (north Sinai, Egypt) between the 10th and 7th centuries BC - Calomino, Eva Amanda; Scaro, Agustina (Journal of Greek Archaeology, 2025)
Between 1995 and 2010, the Argentine Archaeological Mission carried out systematic excavations at the archaeological site of Tell el-Ghaba (northern Sinai, Egypt). It recovered numerous small finds whose study and review seek to contribute to the understanding of the functions that these objects may have had, to the types of activities they may have been involved in, to the understanding of the plastic-compositional repertoire as a whole, and to the interpretation of the themes, meanings and symbolism they may have had.